Book Reviews. (1st August 2012) - ,
Abstract : BOOK REVIEWS Jeffrey Jackson, Paris Under Water: How the City of Light Survived the Great Flood of 1910 (Mike Heffernan) Della Hooke, Trees in Anglo-Saxon England: Literature, Lore and Landscape (Linda Hutton) Innes M. Keighren, Bringing Geography to Book: Ellen Semple and the Reception of Geographical Knowledge (Janice Monk) Sandra Swart, Riding High: Horses, Humans and History in South Africa (Anne N. Greene) Deirdre Jackson, Lion (Jack Dillon) Tom Howells and Duncan McCorquodale (eds.), Mapping America: Exploring the Continent (Andrew Ryder) Jessica B. Teisch, Engineering Nature: Water, Development, and Global Spread of American Environmental Expertise (William D. Rowley)